Use of recycled asphalt in mixtures for pavement base and subbase layers - Lins, Raphael Britto Moura; Póvoas, Yêda Vieira; Silva Júnior, Micael Justino da; Vieira Filho, José Orlando (National Journal of City Management, 2025)
Objective – This research aims to evaluate the mechanical performance of mixtures composed of natural soil and Reclaimed Asphalt Pavement (RAP) for application in pavement base and sub-base layers. Methodology – Laboratory tests were conducted, including grain size distribution, Atterberg limits, compaction, and California Bearing Ratio (CBR) on samples of natural soil and soil/RAP mixtures, replacing the soil with 30%, 40%, and 50% RAP. Additionally, mixtures with Construction and Demolition Waste (CDW) replacing RAP in the same proportions were tested, as well as RAP/stone dust/crushed stone mixtures in the ratios of 70%/30%/0%, 60%/40%/0%, and 50%/40%/10%. Originality/Relevance – The study presents technical laboratory analyses involving low-support-capacity soils, aiming to enhance their performance for use in pavement base and sub-base layers. The inclusion of different material types and mix proportions provides a broader range of performance outcomes. Results – The incorporation of RAP and CDW into natural soil improves its geotechnical properties, making it more suitable for pavement applications, with CBR values increasing by up to six times. RAP was especially effective in improving load-bearing capacity, making it suitable for sub-base layers. Moreover, combining RAP with crushed stone met the requirements for base layers under both light and heavy traffic, offering a sustainable and technically viable pavement solution with increased durability and reduced consumption of natural resources. Theoretical/Methodological Contributions – This study offers significant theoretical contributions by advancing the understanding of stabilizing silty and clayey soils using recycled materials, highlighting the superior performance of RAP over CDW in terms of strength and support capacity. Methodologically, the research stands out for employing standardized DNIT testing procedures, evaluating various material compositions, and integrating technical and sustainability criteria. The findings suggest practical and environmentally responsible alternatives for use in pavement base and sub-base layers, including those subjected to heavy traffic, with strong applicability in road engineering. Social and Environmental Contributions – Considering the shortage of road infrastructure and the limited availability of natural paving materials, the reuse of asphalt waste (RAP) emerges as a sustainable solution. This approach helps reduce environmental liabilities, encourages the reuse of discarded materials, and supports the development of national infrastructure, generating both social and environmental benefits.